Appraising the opportunities and challenges of modular construction in Malaysia - Kho, Hui Yi (2023)
The rising of construction waste, emissions of greenhouse gases, project delays and site accidents have alerted the construction stakeholders to look for alternative construction methods. Modular Construction is a modern construction technology where the building elements are produced in a controlled environment and transported to the site for installation. This study aims to investigate the opportunities and challenges of modular construction in Malaysia and bridge the knowledge gap by developing statistical correlations between the challenges and strategies. Following a comprehensive literature review, 20 opportunities of modular construction, 10 challenges of modular construction and 10 strategies to enhance the implementation of modular construction had been identified. 120 responses were collected from the developers, consultants and contractors within the Klang Valley area. The Mean Ranking showed the five most significant opportunities of modular construction were 1) improve project schedule and productivity; 2) better quality; 3) cost-efficient and effective; 4) sustainable; and 5) better occupational safety and health. Besides, 1) transportation constraint; 2) lack of skilled personnel; time-consuming planning and design; 4) high initial cost; and 5) lack of social knowledge were the five most critical challenges. Meanwhile, the three most effective strategies were 1) government incentives and subsidies; 2) training and education; and 3) research and development. Moreover, the government incentives and subsidies; training and education, establish effective logistic and supply chain management; and research and development were found to be significant correlated with the challenges through Spearman’s Correlations test. Lastly, the Factor Analysis disclosed four underlying factors relating to the opportunities, namely corporate social responsibilities; efficient project control; climate and resources consumption; and competitiveness. The construction industry should promote sustainable development through modular construction to make contribution to the society and natural environments. These findings can serve as a reference point for CIDB to facilitate modular construction in Malaysia and to raise the awareness of sustainable development among the construction stakeholder and public.